2021
DOI: 10.1029/2021pa004243
|View full text |Cite
|
Sign up to set email alerts
|

Wetter Subtropics Lead to Reduced Pliocene Coastal Upwelling

Abstract: One particularly intriguing feature of proxy reconstructions of Pliocene sea surface temperatures (SSTs) is the dramatically higher temperatures inferred at several midlatitude coastal upwelling sites. Midlatitude coastal upwelling today occurs along the eastern boundaries of the Atlantic and Pacific basins and results in narrow strips of cold SST extending 10-50 km off the coasts (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 146 publications
1
12
0
Order By: Relevance
“…Paleobotanic evidence also indicates higher levels of rainfall to the south of the Oregon‐California border (Thompson, 1991; Thompson & Fleming, 1996). Figure 1 shows a map summarizing evidence of Pliocene lakes over the western United States (the figure appears as Figure S1 in Fu et al., 2021). Overall, global climate was characterized by wetter subtropical continents, with many modern‐day subtropical desert regions apparently far less arid during Pliocene time (Burls & Fedorov, 2017; Pound et al., 2014; Salzmann et al., 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Paleobotanic evidence also indicates higher levels of rainfall to the south of the Oregon‐California border (Thompson, 1991; Thompson & Fleming, 1996). Figure 1 shows a map summarizing evidence of Pliocene lakes over the western United States (the figure appears as Figure S1 in Fu et al., 2021). Overall, global climate was characterized by wetter subtropical continents, with many modern‐day subtropical desert regions apparently far less arid during Pliocene time (Burls & Fedorov, 2017; Pound et al., 2014; Salzmann et al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For a more comprehensive summary of the global geological evidence, see Fu et al. (2021) and references therein. Previously proposed explanations for wetter Pliocene conditions over the subtropics include atmospheric teleconnections from a warmer Eastern Equatorial Pacific (the so‐called “permanent El Niño” mechanism mentioned above; Ibarra et al., 2018; Molnar & Cane, 2002, 2007; Winnick et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This increase in water vapor, a GHG, amplifies the fundamental pattern of atmospheric circulation change seen in the CO 2 ‐only simulation, resulting in a stronger stationary wave pattern with greater subsidence on the southern California Margin (Figure 10). A recent study also found that expanded wetlands tend to reduce coastal winds that drive upwelling, though evidence of wetland expansion in Pliocene western North America is limited (Fu et al., 2021). However, expanded lakes and other mesic vegetation in western North America may have had a similar influence.…”
Section: Resultsmentioning
confidence: 99%
“…While CO 2 radiative forcing contributes approximately 50% of the temperature signal, we find that the other 50% of the signal derives from the influence of land surface changes, which consist of prescribed vegetation and ice sheet changes. In fact, a recent study shows that introducing idealized wetlands over subtropical continents reduces upwelling‐favorable wind events by weakening the land‐sea surface pressure gradient, helping to recreate warmer coastal temperatures indicated for the early Pliocene (Fu et al., 2021). This highlights the importance of ensuring accurate reconstructions of vegetation and ice cover for greenhouse climate states, since these non‐CO 2 boundary conditions may exert a powerful influence on regional climates even in remote, non‐terrestrial settings.…”
Section: Discussionmentioning
confidence: 99%